Industrial training report: Lawas District Council / Faridzul Azli Mohd. Tahir - Mohd. Tahir, Faridzul Azli (University Technology MARA Sarawak, 2013)
Lawas District is a county located in Limbang, Sarawak. Lawas District rating stragetik the bordering states of Sabah and Brunei Darussalam and Labuan Federal Territory Lawas District as a rural tourist especially the people of Brunei. The hilly nature and greenery make Lawas district floranya rich with all the fruit crops and vegetables. One of the unique Lawas District is the production of apples and oranges that can be found in the highlands of Ba'kelalan. To ensure the smooth running of regional development, the existence of Lawas District Council is appropriate to ensure not miss Lawas District in the development of this State. Lawas history according to Chang Pat Foh in ‘ Legends and History Of Sarawak‘ are as follows: Originally, Lawas was part of Brunei but Sultan of Brunei leased it to the British North Borneo Company. It was only on 5.1.1905, the Lawas River area was annexed to Sarawak from British North Borneo Company with the consent from the British Goverment. Lawas, in Bahasa Malaysia means “Luas”, is spacious and wide area. In the olden days, people in the area grouped themselves together in the spacoius area to settle down there and hence, a township was born. However, there is another legend. Long time ago, a group of merchants was attacked and chased after by the pirates at Kuala Lawas. They escaped and retreated to the present site of Lawas Town. At the time the area was thick jungle and they managed to hide themselves there. The pirates could not find them and they returned to the sea. the merchants felt relief, safe and secure. In local malay dialect, it was called “Lawas” (relief, safe and secure) until today.